The Ethnobiology of Merarik Kodeq in Lombok - Kusuma, Anindita SHM; Putri, Hestiani; Putri, Luh Putu Sasmita Sridewi; Murthi, I Wayan Aditya Arya; Hadawiyah, Laelatun; Arofah, Zainul (Jurnal Ilmiah Profesi Pendidikan, 2025)
The tradition of Merarik Kodeq, or early marriage, remains a serious issue for the Sasak community in West Nusa Tenggara. The aim of this study is to explore the ethnobiological perspective on the Merarik Kodeq culture in West Lombok and to identify the efforts made by the local government of West Lombok Regency to curb the growing prevalence of Merarik Kodeq. This study uses a descriptive qualitative method. Informants were selected using purposive sampling based on specific criteria, namely couples who married at an early age. The results show that the average age of early marriage in Sekotong Barat Village is 16–17 years. At this age, reproductive organs are still in the developmental stage, especially the female reproductive system, which functions as the place for fetal development. Therefore, pregnancies occurring at this age pose a high risk of miscarriage, birth defects, and even maternal and infant mortality. In response to the increasing rate of Merarik Kodeq or early marriage, the local government initiated a movement known as the Anti-Merarik Kodeq Movement.